A new frequency reconfigurable microstrip patch antenna based on implanting tuning capacitors - Mushreq Abdulhussain Shuriji; Raad Hamdan Thaher (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
The research proposed a new electrically reconfigurable microstrip antenna via a lumped capacitor. Instead of using a varactor diode as a switching circuit which leads to a more complicated design by adding biasing circuits, our suggested antenna design has offered straightforward tuning skills. The projected design has resolved many issues such as a reduction in system complexity by eliminating the biasing circuit, limiting the use of advanced manufacturing devices through using the external circuit to implant or detach the capacitor into or from the antenna main structure, and impedance matching supported with optimum physical structure calculations. The reconfigurable antenna has been modeled and designed using computer simulation technology (CST) software, the prototype antenna has been implemented practically and tested using a spectrum analyzer. The suggested compact antenna has a size of 42×33×0.53 mm3, and supports multi-operational frequency bands (C, X, Ku, and K) which is suitable for modern communication technologies such as Wi-Fi, 5G, and satellite communication.